2009
DOI: 10.1007/s11242-008-9332-7
|View full text |Cite
|
Sign up to set email alerts
|

A Summary of New Predictive High Frequency Thermo-Vibrational Models in Porous Media

Abstract: In this paper, we consider the effect of mechanical vibration on the onset of convection in porous media. The porous medium is saturated either by a pure fluid or by a binary mixture. The importance of a transport model on stability diagrams is presented and discussed. The stability threshold for the Darcy-Brinkman case in the Ra T c -R and k c -R diagrams is presented (where Ra T c , k c and R are the critical Rayleigh number, the critical wave number and the vibration parameters, respectively). It is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Further, this leads to the appearance of a modified gravity, collinear with actual gravity, in the form of a time-periodic gravity field perturbation and is known as gravity modulation or G-jitter in literature. Some of the documented works on gravity modulation in recent times include Yang (1997), Malashetty and Padmavathi (1997), Rees and Pop (2000, 2001, 2003, Malashetty and Basavaraj (2002), Govender (2004Govender ( , 2005a, Kuznetsov (2005Kuznetsov ( , 2006a, Siddhavaram and Homsy (2006), Strong (2008a,b), Razi et al (2009), Purusothaman (2009), Vanishree (2010), Saravanan and Arunkumar (2010), Malashetty and Swamy (2011), and Sivakumar (2010, 2011), . However, most of the studies on thermal instability in a porous medium with gravity modulation concern only linear stability and hence address only questions on onset of convection.…”
Section: Introductionmentioning
confidence: 99%
“…Further, this leads to the appearance of a modified gravity, collinear with actual gravity, in the form of a time-periodic gravity field perturbation and is known as gravity modulation or G-jitter in literature. Some of the documented works on gravity modulation in recent times include Yang (1997), Malashetty and Padmavathi (1997), Rees and Pop (2000, 2001, 2003, Malashetty and Basavaraj (2002), Govender (2004Govender ( , 2005a, Kuznetsov (2005Kuznetsov ( , 2006a, Siddhavaram and Homsy (2006), Strong (2008a,b), Razi et al (2009), Purusothaman (2009), Vanishree (2010), Saravanan and Arunkumar (2010), Malashetty and Swamy (2011), and Sivakumar (2010, 2011), . However, most of the studies on thermal instability in a porous medium with gravity modulation concern only linear stability and hence address only questions on onset of convection.…”
Section: Introductionmentioning
confidence: 99%
“…In some related studies in fluid media, Razi et al [11] showed that the asymptotic analysis results in a closed form relation for the stability threshold. In order to obtain such a relation, a regular perturbation method with the wave number as the small parameter is performed (for simplifying the procedure), we drop the tilde symbol and we expand (ψ , θ, η, ϕ , σ) as…”
Section: Limiting Case Of the Long-wave Mode Instabilitymentioning
confidence: 99%
“…(19) and (20) are solved then to obtain the marginal curves of Ra T against α for S and SH modes respectively. Prior to that convergence of the continued fractions was verified numerically and the continued fractions were truncated once the desired precision (10 −4 ) is achieved.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…A brief review of the findings related to the above subject have been given by Razi et. al [19]. Recently, Strong [20] brational thermosolutal convection in a horizontal Darcy porous layer and constructed the neutral curves for synchronous, subharmonic and quasiperiodic instability modes.…”
Section: Introductionmentioning
confidence: 99%